Soil aggregates regulate microbial drivers of phosphorus fractions under mowing and phosphorus addition - Li, Xiuping; Cui, Haiying; Wang, Shanling; Hu, Baoshuang; Zhai, Huiliang; Hu, Jiaxin; Peng, Xia; Shakir, Muhammad; Sun, Wei (Frontiers in Microbiology, 2025)
Microorganisms play a vital role in maintaining ecosystem structure and function by mediating the dynamics of phosphorus (P) fractions under land-use intensification. However, microbial properties vary considerably across different soil aggregate sizes, making it challenging to determine how microorganisms regulate P fractions in response to mowing and P addition. To address this knowledge gap, we conducted an 8-year field study in a meadow steppe in Northeast China to examine the effects of mowing, P addition, and their interaction on P fractions across soil aggregate sizes. The results indicated that the interaction between mowing and P addition increased total P across soil aggregates. Specifically, this interaction enhanced available P (the sum of labile Pi and labile Po) by 74.13, 55.01, and 9.50% in large macroaggregates (LMA), small macroaggregates (SMA), and microaggregates (MA), respectively. In LMA, increases in moderately labile Pi, moderately labile Po, and residual P were driven by a decreased microbial biomass carbon to microbial biomass phosphorus (MBC: MBP) ratio, which was reduced by P addition. In SMA, P addition and mowing increased labile Po, labile Pi, and moderately labile Pi by enhancing plant richness. In MA, P addition not only increased labile Po and moderately labile Pi by stimulating plant belowground biomass (BGB) but also enhanced residual P through elevated alkaline phosphatase (ALP) activity. These findings highlight the critical role of soil aggregates in regulating the dynamics of microbially driven soil P fractions. Overall, the distinct responses of P fractions and their dominant drivers provide valuable insights into P cycling in grasslands and support the development of sustainable land management strategies.